2021
DOI: 10.1111/bju.15589
|View full text |Cite
|
Sign up to set email alerts
|

Urine DNA for monitoring chemoradiotherapy response in muscle‐invasive bladder cancer: a pilot study

Abstract: Accumulating evidence implies the utility of DNA-based urine biomarkers for initial detection of bladder cancer (BC) and surveillance of non-muscle-invasive BC [1,2]. We have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…All the above studies illustrate that urinary DNA markers perform well in the detection and surveillance of BLCA. Several studies analysed changes in BLCA‐associated DNA mutations in the urine of patients with MIBC before, during and after treatment with chemotherapy or chemoradiotherapy and suggested that measuring tumour‐specific DNA mutations in urine might be a valuable tool for monitoring treatment response 124,125 . However, whether urinary DNA markers could contribute to monitoring treatment responses in patients with BLCA remains to be further evaluated.…”
Section: Opportunities Of Urine‐based Liquid Biopsy In Blcamentioning
confidence: 99%
“…All the above studies illustrate that urinary DNA markers perform well in the detection and surveillance of BLCA. Several studies analysed changes in BLCA‐associated DNA mutations in the urine of patients with MIBC before, during and after treatment with chemotherapy or chemoradiotherapy and suggested that measuring tumour‐specific DNA mutations in urine might be a valuable tool for monitoring treatment response 124,125 . However, whether urinary DNA markers could contribute to monitoring treatment responses in patients with BLCA remains to be further evaluated.…”
Section: Opportunities Of Urine‐based Liquid Biopsy In Blcamentioning
confidence: 99%
“…Two studies have examined PLEKHS1 and TBC1D12 mutations in the urine of BC patients and non-cancer control subjects; however, both had limited samples sizes and used healthy controls 11,12 . The variant allele frequencies of the non-coding hotspots in urine have also been shown to decrease following chemoradiotherapy in BC patients and following upper-tract tumour resection 13,14 .Multiple studies have shown that coding mutations in BC-associated genes and the TERT promoter can be used for the non-invasive detection of BC 11,15,16 . We hypothesized that non-coding mutation hotspots may also…”
mentioning
confidence: 99%
“…Two studies have examined PLEKHS1 and TBC1D12 mutations in the urine of BC patients and non-cancer control subjects; however, both had limited samples sizes and used healthy controls 11,12 . The variant allele frequencies of the non-coding hotspots in urine have also been shown to decrease following chemoradiotherapy in BC patients and following upper-tract tumour resection 13,14 .…”
mentioning
confidence: 99%